A community for students.

Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing


  • one year ago

A missile is launched from the ground. Its height, h(x), can be represented by a quadratic function in terms of time, x, in seconds. After 1 second, the missile is 58 feet in the air; after 2 seconds, it is 112 feet in the air. Complete the height function, h(x), for this situation.

  • This Question is Open
  1. ybarrap
    • one year ago
    Best Response
    You've already chosen the best response.
    Medals 1

    Since h(x) is a quadratic, we have $$ h(x)=ax^2+bx+c $$ Where a,b and c are constants to be determined by the information in the question, x is the time in seconds and h(x) is the height of the missile at time x. We are given that at time x=1 that h(1)=58, that is, the missile after 1 second is 58 feet above the surface. Using our 1st equation above and plugging in the given values for x and h(x): $$ 58=a1^2+1b+c=a+b+c $$ We see that we have 3 constants to solve for but we only have one equation so far. We also can assume that at time x=0 that h(0)=0. This is saying that the missile starts out on the ground. This implies that c=0 because using the 1st equation above: $$ 0=a\times 0^2+b\times 0 + c\\ \implies c=0 $$ We are also given that at time x=2, h(2)=112. So now we have $$ 112=a2^2+b2=4a+2b\\ \implies 56=2a+b $$ We now have two equations and two unknowns: Solvable: $$ 58=a+b\\ 56=2a+b $$ Now subtract them: $$ 58-56=a-2a+b-b=-a\\ a=-2 $$ Using any of our new equations, we can now get \(b\): $$ 58=-2+b\\ 56=-4+b $$ Does this make sense?

  2. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy

Your question is ready. Sign up for free to start getting answers.

spraguer (Moderator)
5 → View Detailed Profile

is replying to Can someone tell me what button the professor is hitting...


  • Teamwork 19 Teammate
  • Problem Solving 19 Hero
  • You have blocked this person.
  • ✔ You're a fan Checking fan status...

Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.

This is the testimonial you wrote.
You haven't written a testimonial for Owlfred.